An analytical study of gallstones by Fourier transform infrared spectroscopy technique - Bilagi, Anil; Godhi, Ashok S. (International Surgery Journal, 2022)
Background: Cholelithiasis continues to be a serious human health concern and presently cholecystectomy is the only adopted standard treatment option. Gallstones’ chemical structures differ in different demographic groups. Accurate analysis of the constituents of gallstones may help us to understand their etiopathogenesis. Fourier transform infrared spectroscope (FTIR) can identify the composition of gallstones by creating a spectrum of infrared absorption. Methods: A hospital based one year observational study was conducted in KLES’ Dr. Prabhakar Kore Hospital and Medical Research Centre, Belagavi and 120 gallstones were collected post laparoscopic/open cholecystectomy. After FTIR spectroscopic analysis gallstones were classified based on the FTIR spectrum peaks. Results: Cholesterol, bilirubin and calcium carbonate are the components identified based on the standard FTIR spectrum characteristics with cholesterol being the commonest followed by bilirubin. Brown colored stones were more common followed by black. We classified gallstones into 3 groups based on FTIR analysis as: pure cholesterol stones, pure bilirubin stones and mixed type of stones. Mixed type of gallstones containing cholesterol and bilirubin were more common. Conclusions: The study concludes cholelithiasis is common in females and in age group more than 40 years. Mixed types of gallstones are the commonest. Cholesterol followed by bilirubin are the major constituents of the gallstones.